Analysis and interpretation of the Islamic Republic of Iran's votes at the Court of Arbitration for Sport (CAS) - Madine Asadi; Mohammad javad Javid (Research in Sport Management and Marketing, 2024)
Purpose: Sports tournaments are now massive events watched by millions of people all over the globe. The Court of Arbitration for Sport (CAS) is an institution independent of any sports organization that provides services to facilitate the resolution of sports-related disputes through arbitration or mediation using procedural rules tailored to the unique needs of the sports world. In this paper, the author has attempted to look into and determine the reason of the outcomes of the votes made by this institution, taking into account the significance of the CAS on sports in the Islamic Republic of Iran. Methods: The court rulings involving Iranian athletes have been particularly analyzed in this article, with a focus on the rulings that helped Iranian athletes win. The textual content analysis approach was used in this investigation. For examining various communications, including ideas, interviews, documents, observations, and written texts, content analysis is a useful and effective method.Results: The current research studied and analyzed judgements made by the CAS on matters involving Iranian sports. Despite the fact that fewer than 25% of the lawsuits involving Iranian parties ended with a win for that side, the data revealed that there were indications of Iranian cases failing even in this small proportion.Conclusion: The Iranian side usually realizes that the other side is right and has a small likelihood of winning, therefore simply complains to the CAS to purchase time, which is one of the key reasons why Iran's cases before the CAS fail